2022
DOI: 10.1097/mpg.0000000000003622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Psyllium in Pediatric Irritable Bowel Syndrome

Abstract: Objective: Pediatric irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder with variable response to various therapeutic agents. Psyllium has been proven to be effective in adults; however, there is no study in children. The objective of this study is to evaluate the efficacy of psyllium husk as compared to placebo in pediatric IBS patients. Methods: In this double-blind randomized controlled trial, 43 children were assigned to psyllium arm (Group A) and 38 into placebo arm (Group B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…A 2022 systematic review and meta‐analysis identified six studies evaluating the role of prebiotics in the management of FAPD in children 39 . Three trials examined children diagnosed with irritable bowel syndrome (IBS) according to the Rome II, III, and IV criteria 31,32,40 . In the randomized, double‐blind, controlled, and prospective study from Turkiye, included 71 children between the ages of 4 and 16 years who were diagnosed with IBS according to the Rome III criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2022 systematic review and meta‐analysis identified six studies evaluating the role of prebiotics in the management of FAPD in children 39 . Three trials examined children diagnosed with irritable bowel syndrome (IBS) according to the Rome II, III, and IV criteria 31,32,40 . In the randomized, double‐blind, controlled, and prospective study from Turkiye, included 71 children between the ages of 4 and 16 years who were diagnosed with IBS according to the Rome III criteria.…”
Section: Resultsmentioning
confidence: 99%
“…39 Three trials examined children diagnosed with irritable bowel syndrome (IBS) according to the Rome II, III, and IV criteria. 31,32,40 In the randomized, double-blind, controlled, and prospective study from Turkiye, included 71 children between the ages of 4 and 16 years who were diagnosed with IBS according to the Rome III criteria. Administration of synbiotics and probiotics resulted in significant improvements for belching-abdominal fullness, bloating after meals, and constipation when compared to prebiotics.…”
Section: Prebiotics and Functional Abdominal Pain Disorders (Fapd)mentioning
confidence: 99%
“…A double-blind RCT in 2022 by Menon et al was conducted to assess the efficacy of oral psyllium in IBS compared with placebo. There was a statistically significant reduction in the severity of symptoms in the psyllium group versus the placebo group at the end of 4 weeks and treatment was determined to be equally effective in different IBS subtypes, constipation, diarrhea, and mixed [20 ▪ ].…”
Section: Treatment and Managementmentioning
confidence: 94%
“…We thank van Tilburg et al (1) for their interest regarding our randomized controlled trial in children with irritable bowel syndrome (IBS) (2). The authors have raised a concern on applying IBS Severity Scoring System (IBS‐SSS) in children (3).…”
Section: Dear Editormentioning
confidence: 99%